Left ventricular assist device-related infections: a multicentric study - Siméon, S.; Flécher, E.; Revest, M.; Niculescu, M.; Roussel, J.-C.; Michel, M.; Leprince, P.; Tattevin, P. (Clinical Microbiology and Infection, 2017)
Abstract Objectives The implantable left ventricular assist device (LVAD) is a major therapeutic development for end-stage heart failure in selected patients. As their use is expanding, infectious complications are emerging, with limited data available to guide their management. We aimed to better characterize LVAD-related infections. Methods We enrolled all consecutive patients diagnosed with LVAD-related infections in three referral centres in France, using a standardized definition of infections in patients with LVAD. Data were collected from medical charts using a standardized questionnaire. Results Between 2007 and 2012, 159 patients received LVAD for end-stage heart failure. Among them, 36 (22.6%; 5 women, 31 men) presented at least one infectious complication, after a median time of 2.9 months from LVAD implantation (interquartile range, 1.8–7.5), with a median follow up of 12 months (interquartile range 8–17). Main co-morbidities were alcoholism (33%), diabetes (11%) and immunosuppression (11%). Mean age at implantation was 51 (±11) years. LVAD were implanted as bridge-to-transplantation (n=22), bridge-to-recovery (n=8), destination therapy (n=4), or unspecified (n=2). LVAD-related infections were restricted to the driveline exit site (n=17), had loco-regional extension (n=13), or reached the internal pump (n=3). The main bacteria isolated were Staphylococcus aureus (n=20), coagulase-negative staphylococci (n=7), Enterobacteriaceae (n=14), Pseudomonas aeruginosa (n=10) and Corynebacterium sp. (n=7), with polymicrobial infections in 19 cases. LVAD could be retained in all patients, with the use of prolonged antibacterial treatment in 34 (94%), and debridement in 17 (47%). One patient died due to LVAD-associated infection. Conclusions LVAD-related infections are common after LVAD implantation, and may be controlled by prolonged antibiotic treatment.